2018
DOI: 10.1186/s13567-018-0513-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel CAV derived cell-penetrating peptide efficiently delivers exogenous molecules through caveolae-mediated endocytosis

Abstract: Cell-penetrating peptide (CPP) is a promising cargo for delivering bioactive molecules. In this study, the N terminus of VP1 from chicken anemia virus, designated as CVP1, was found to carry enriched arginine residues with α-helix. By confocal imaging, flow cytometry and MTT assay, we identified CVP1 as a novel, safe and efficient CPP. CVP1-FITC peptide could entry different types of cells tested with dose dependence, but without cytotoxic effects. Compared with TAT-FITC peptide, the CVP1-FITC peptide showed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…4). Dr. Hu reported that the N-terminus of the VP1 protein consists of enriched arginine residues similar to HIV-TAT [23]. The sequence has an efficient cell-penetrating activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Dr. Hu reported that the N-terminus of the VP1 protein consists of enriched arginine residues similar to HIV-TAT [23]. The sequence has an efficient cell-penetrating activity.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this finding, the possible functional domain of VP1, especially in terms of the cellular localization, is not well understood, although some researchers have demonstrated the subcellular distribution of VP1 in cells using transient protein expression and immunofluorescence assays [11, 22]. The N-terminus of VP1 has been reported to possess a cell-penetrating activity [23]. Therefore, further research into and analysis of protein trafficking of VP1 may provide more information for elucidation of the biological function of nuclear localization of CAV viral proteins in virus replication.…”
Section: Introductionmentioning
confidence: 99%
“…It is now generally recognized that CPPs at low concentration, and when conjugated to cargo, are taken up by cells in an energy-dependent manner. Endocytosis as a mechanism for the Clathrin-and caveolae-independent endocytosis TAT-protein conjugates [60] unconjugated TAT [83] TAT-protein conjugates [92,93] p18 and p28 azurin fragments [98,99] poly-arginines [65][66][67] MPG/siRNA conjugate [84,85] proline-rich CPPs [94] transportan [95] NickFect51 [77] NickFect51-cargo conjugates [77] transportan-10-protein conjugates [95] low molecular weight protamine (LMWP)/siRNA conjugate [104] octa-arginine (R8) [44] PepFect14/DNA conjugate [97] p18 and p28 azurin fragments [98,99] CVP1 [100] transport of CPPs across cellular membranes was suggested in 2003, after Richard et al [38] pointed to the possible errors in the results describing direct translocation due to the experimental methods used. Since this initial report, studies which described the active transport of CPPs emerged.…”
Section: Endocytosis As An Active Pathway For Cpp Uptakementioning
confidence: 99%
“…More recently, the N-terminus of VP1 from chicken anemia virus (CAV), designated as CVP1, was shown to act as CPP and efficiently deliver exogenous molecules through caveolae-mediated endocytosis [100]. While employing several endocytic inhibitors, methylated β-cyclodextrin significantly reduced the uptake of CVP1, which implies caveolae-mediated endocytosis as a possible internalization mechanism.…”
Section: Caveolae-mediated Endocytosis and Cppsmentioning
confidence: 99%
“…This pathway is involved in the uptake of TAT, proline-rich CPPs, PepFect14/DNA conjugate, p18 and p28 azurin fragment [32]. A recent study also revealed that a novel chicken anemia virus derived CPP, designated as CVP1, effectively delivered β-glycosidase, poly (I:C) and plasmid into HCT116 cells via CvME [33]. Finally, CME begins with the initiation of endocytic events by formation of vesicles in phosphatidylinositol 4,5-biphosphate-rich regions of plasma membrane after interaction of peptides with specific cell surface receptors.…”
Section: Molecular Mechanisms Of Delivery Of Cell Penetrating Peptidesmentioning
confidence: 99%